Increasing Students Intercultural Awareness Using Film as the Media in the EFL Classroom - Kartikasari, Yeni Dyah Nur; Retnaningdyah, Pratiwi; Mustofa, Ali (International Journal for Educational and Vocational Studies, 2019)
The study was aimed to obtain information regarding to the teachers strategy and students aspects of Intercultural Awareness (ICA) perceived from CCC through film. It was qualitative study and data of the study were taken from documentations which consisted of observation sheets, field notes, and students journal writing with guided questions in three phases: before, during and after viewing the film. Based on data analysis, the result shows that there were four categories in the strategies of ICA the teacher developed through film in the EFL classroom. The teacher also tended to apply the QAR strategies as well as it aimed at improving students reading comprehension before, during and after watching the film which showed six steps. The six steps were by visualizing to the information to students own experience, recalling students past experiences, clarifying to students behavior towards different cultures from their own, locating the information from the film, imagining to the position of the characters in the film, and summarizing the film to the positive and negative sides. Another finding was found that from twenty-one aspects, there was ˜respect to others as major key of all aspects of ICA emerged. The two findings contributed much for intercultural study.